Analysis Of Elements Of The Iranian Story In The Story Of Rustom And Suhrab - A Stylistic Study: بررسی عناصر قصه ایرانی در داستان رستم و سهراب، با رویکرد سبک‌گرایی (Journal of the College of Languages (JCL), 2020)
Iranian stories have been one of the most important aspects of Iranian society's culture and have reflected us as a mirror of all its cultural, societal and political dimensions.Among the important elements of the story can be the creation of space and the movement and the creation of characters and conflict and content and the angle of vision and landscape, language and subject. Studying the elements of the story leads to more understanding and determining the strength and skill of the author by studying the elements of his story. The story of Rustom and Suhrab is also one of the many stories in which the elements of the story are often noticed and show the skill of the great professor Al-Fardousi to benefit from these elements.Some of the objectives that the author sought in this article can be summarized in the following axes: The first axis: Presentation of an intellectual form of the book "Shah Nama" for Paradise as a model for all aspects of Iranian culture,The second axis: Presenting a new research model for researchersAnd the third axis: the knowledge of Iranian culture more accurately through the text of the Shah .The method and direction of this research is based on analytical descriptive method.Fardousi has combined the two styles of enthusiasm and singing with each other and with great skill and has done his work with great creativity and art in his unmatched formulation of vocabulary and compositions. The absence of the influence of the Arabic language on the poems of the "Shah" and its exploitation of elements such as the use of proverbs, representations and testimony from the counterpart, his commitment to the music and the melody of modernity, as well as the commitment to brevity and shortening of speech and exaggeration. "The Shah" has made all the language of this literary mission distinct and distinct. Although the book "Shah Nama" has been studied and research from different dimensions and angles, but there are still new areas of research did not address anyone. قصه های ایرانی یکی از مهمترین جلوه های فرهنگ جامعه ایران بوده و همواره همچون آیینه ای تمامنما، ابعاد فرهنگی، جامعه شناختی و سیاسی آن را برای ما منعکس کرده است. از عناصر مهم داستان میتوان به فضاسازی، پیرنگ، شخصیتپردازی، کشمکش و گرهافکنی، درونمایه، زاویه دید، صحنه، زبان و موضوع اشاره کرد. بررسی عناصر داستان باعث فهم بیشتر آن می‌شود و قدرت و مهارت خالق اثر، از راه بررسی عناصر داستان او مشخص می‌گردد. داستان رستم و سهراب نیز از جمله داستان‌هایی است که عناصر داستانی در آن موج می‌زند و مهارت استاد بزرگ، فردوسی را در بهره‌گیری از این عناصر به نمایش می‌گذارد. برخی از اهدافی که در این جستار مورد نظر نویسنده بوده را می توان در محورهای زیر خلاصه نمود: محور نخست ارائه یک مدل فکری یا اندیشگانی از شاهنامه فردوسی به عنوان آیینه تمام نمای فرهنگ پارسی، دوم ارائه یک الگوی پژوهشی جدید و تازه برای دانش پژوهان و سوم شناخت هر چه دقیق تر فرهنگ ایرانی از طریق متن شاهنامه. شیوه و رویکرد این پژوهش بر مبنای روش وصفی تحلیلی می باشد.فردوسی دو سبک ادبی حماسه و غنا را استادانه با هم درآمیخته ودر واژه‌سازی‌ها و ترکیب‌های بی‌نظیرش بسیار خلاقانه و هنرمندانه عمل کرده است. عدم تاثیر زبان عربی بر اشعار شاهنامه، بهرهگیری از عناصری چون ارسالالمثل و تمثیل، استفاده از مناظره، رعایت موسیقی و آهنگ کلام، ایجاز و اختصار در سخن و اغراق، و نیز بیان نکات اخلاقی و تربیتی، در جام داستان‌های شاهنامه، زبان این اثر شاهکار را متمایز و ممتاز گردانیده است. با آن که شاهنامه از ابعاد و زوایای مختلفی مورد بررسی و کنکاش قرار گرفته است، لیکن هنوز زمینه های تحقیقی تازه و بکری در آن موجود می باشد.